1988
DOI: 10.1099/0022-1317-69-5-1079
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vitro Reactivation of Herpes Simplex Virus Type 2 from Latently Infected Guinea-pig Neural Tissues by 5-Azacytidine

Abstract: SUMMARY5-Azacytidine (5-AZC) reduces cytosine methylation in DNA and has been reported to activate quiescent virus genes. Treatment of explant cultures of latently herpes simplex virus type 2 (HSV-2)-infected guinea-pig dorsal root ganglia and spinal cords in vitro with 5-AZC significantly enhanced the rate of HSV recovery. Both the number of isolates from ganglia (P < 0.001) and the rate of recovery (P < 0.001) were significantly increased with the addition of 50 ~tM-5-AZC to explant cultures. Increased virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Detection of latent virus from additional animals might have been enhanced by incorporation of demethylating agents in the culture medium (Stephanopoulos et al, 1988) or by hybridization techniques (Stanberry et al, 1985 b). We and others have previously reported that HSV may also establish a latent infection in guinea-pig genital skin (Stanberry et al, 1985b;Bernstein & Kappes, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of latent virus from additional animals might have been enhanced by incorporation of demethylating agents in the culture medium (Stephanopoulos et al, 1988) or by hybridization techniques (Stanberry et al, 1985 b). We and others have previously reported that HSV may also establish a latent infection in guinea-pig genital skin (Stanberry et al, 1985b;Bernstein & Kappes, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Youssoufian et al demonstrated that a latent infection of chicken lymphocytes with HSV-1 was associated with DNA methylation and that virus could be induced to reactivate in this in vitro system following treatment of the lymphocytes with 5-azacytidine, an inhibitor of DNA methyltransferase (36). Two other studies demonstrated that use of methyltransferase inhibitors enhanced the reactivation of HSV-2 from latently infected guinea pig ganglia (5,30). While Dressler and Fraser showed that the HSV-1 genome was not extensively methylated during latency (13), the possibility remained that DNA methylation at discrete sites in the promoters of key regulatory genes could play a role in the regulation of latent transcription.…”
Section: Vol 78 2004 Histone Modifications and Hsv-1 Latent Gene Exmentioning
confidence: 99%
“…The effects of HMBA and DMSO in these systems have been attributed to demethylation, for two reasons. First, addition of 5-azacytidine or L-ethionine also improves reactivation of latent HSV (Whitby et al, 1987;Stephanopoulos et al, 1988), and second, during induction of erythroleukaemic cells, a transient decrease in 5-methylcytosine levels occurs (Razin et al, 1988).…”
Section: Introductionmentioning
confidence: 99%